Learning to read: developing processes for recognizing, understanding and pronouncing written words. (1st March 2006) - Stuart, Morag
Abstract : Major theories of how skilled readers recognize, understand and pronounce written words include processes for phonological recoding (i.e., translating segments of print to their corresponding segments of sound) and processes by which direct access is achieved from printed words to their meanings. If these are the processes employed in skilled reading, then these are the processes which children learning to read must develop in order to become skilled readers. This paper reviews experimental findings relevant to the development of both sets of processes in beginning and early readers.